Failure analysis of type 304 stainless steel amine exchanger sheets in a gas sweetening plant. (October 2017) - Panahi, H.; Eslami, A.; Golozar, M.A.; Ashrafi Laleh, A.; Aryanpur, M.; Mazarei, M.
Highlights: Failure mechanism of a plate type amine exchanger was investigated. Intergranular stress assisted corrosion cracking was the prevalent mechanism of failure. Corrosion and cracking was more sever under the gasket region of the amine exchanger. Abstract: Amine exchangers are widely used in gas sweetening plants for amine solution regeneration process. This study is investigates cracking and leakage of a 304 type stainless steel plate in an amine exchanger unit, used between absorption and stripper towers. In this regard, micro and macro examinations were performed on the plate, and solution was analyzed. Micro cracks were observed on both sides of the plate, especially under the gasket region of the plate. Results showed that the main reason of cracking was intergranular corrosion accompanied by stress. High concentration of Formate in amine solution, and also high level of stress under gasket region, had initiated the intergranular corrosion and cracking.